The police and political development in India - Bayley, David H. (Princeton legacy library., 1969)
As a pervasive and relatively modernized element of Indian society, the police are potentially a powerful vanguard in the establishment of a stable democratic process and a major factor in public attitudes toward the government. Professor Bayley's book, based upon 3,600 interviews during two extended periods of research in India, explores in depth the formative role police play in the maintenance and development of the Indian political system. As a first study of police and political development in a relatively non-modernized country, this book will be a guide for the exploration of a topic critical in the political life of many nations, both developed and underdeveloped. Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.